تأثير التخطيط الاستراتيجي في فاعلية وزارة التجارة العراقية ِ استطلاعية تحليلية لآراء عينة من قياداتها العليا (المجلة العراقية للعلوم الاقتصادية, 2018)
This study is based on two variables, strategic planning and organizational effectiveness where they have been intellectually exposed. Then, it has been tested the impact of strategic planning, as an independent variable, on the variable under study which is the effectiveness of the Ministry of Iraqi Trade. An intentionally sample consists of (30) top leaderships has been tested where their attitudes have been explored and analyzed to verity the nature of strategic planning in the ministry and the extent of its contribution in raising or decreasing its effectiveness. After analysis, it has been confirmed that some of the variables of the sub-study were effective and there were declination of others. Also, it has been acquainted with the positive and negative aspects of the dependent strategic planning process, and came up with recommendation and business mechanisms aim at developing the necessary goals and strategies to achieve the vision of the Ministry of Iraqi Trade.